Pneumomediastinum and Bilateral Pneumothoraces Causing Respiratory Failure after Thyroid Surgery - Michael Koeppen; Benjamin Scott; Joseph Morabito; Matthew Fiegel; Tobias Eckle (Case Reports in Anesthesiology)
We report the first case of severe respiratory failure after thyroid surgery requiring venovenous extracorporeal membrane oxygenation (vvECMO). The patient was a 41-year-old woman with metastatic thyroid cancer. She underwent thyroidectomy, including left lateral and bilateral central neck dissection. During surgery, the patient developed pneumomediastinum with bilateral pneumothoraces. Despite early treatment with bilateral chest tubes and no evidence of a tracheal perforation, the patient developed severe respiratory failure after extubation on the intensive care unit. Because pneumothorax and pneumomediastinum might be more common than reported, and considering increasing cases of thyroid surgery, staff should remain vigilant of pulmonary complications after thyroid surgery.